CHARACTERIZATION OF SAGO PALM-CARBON FIBRE REINFORCED EPOXY HYBRID COMPOSITES - Binti Saad, Safinaz; Salman, Suhad D.; Leman, Zulkiflle; Faraj Alkbir, Munir (Journal of Engineering and Sustainable Development, 2022)
Natural fibres are potential alternatives to synthetic fibres. Sago palm is a new type of natural fibre and has the potential same as other existing natural fibres. In this study, the mechanical properties of sago palm/carbon fibre reinforced with epoxy hybrids were studied. Impact tests were conducted to study the impact properties of sago palm-carbon fiber-reinforced epoxy hybrid composites. The hybrid composites contain woven sago palm fibre and carbon fibre reinforced with epoxy resin is produced by the vacuum compaction method. Each sample was prepared with different volume fractions such as 40%, 64% and 91% of composition sago palm fibre. After the preparation of composite material, mechanical properties tests were studied on the prepared sample. In addition, by using Scanning Electron Microscope Tests, the failure mode is investigated. It can be concluded that 40% of sago palm fiber contains to have the best impact behavior compared to the 64% and 91% of sago palm fiber loading because it’s high in impact resistance.